Eudaimonia in the relationship between human and nature: A systematic literature review - Lima, Pedro Augusto Bertucci [UNESP]; Mariano, Enzo Barberio [UNESP] (Elsevier, 2022)
Sustainable development is a well-known and much studied topic, the application of many different approaches to which has led to continual debate about its true meaning and feasibility. A eudaimonic well-being approach might offer a new perspective to these discussions. This research aimed to understand the current state of the relationship between eudaimonic well-being and nature to establish whether sustainability can be conceptualized based on this perspective. In order to accomplish this aim, the study carried out a systematic literature review, using the ‘Preferred Reporting Items for Systematic Reviews and Meta-Analysis’ method. The available literature was screened and the 50 articles selected through this process were mapped by means of bibliometric, methodological, and content analyses. This threefold analysis identified, for each article, the region where the empirical investigation took place; the main method used; key information about the relationship between eudaimonic well-being and nature; and the theories presented with the aim of explaining the reasons for the positive or negative relationships identified. The findings indicated that contact with nature, preservation behavior and nature interdependency were the three main aspects studied in the literature, in terms of the interactive relationship between eudaimonic well-being and nature. Considering that several studies identified a positive outcome from the contact with, preservation, and interdependence of nature, the research concluded that eudaimonic well-being is an important approach in support of the promotion of sustainable development.
Keywords: Environment; Eudaimonic; Happiness; Nature; Sustainable development